Introduction of solids: directions for future resource development - Begley, Andrea; Keegan, Elizabeth (Wiley-Blackwell, 2016)
A lack of adherence by mothers to the introduction of solids guidelines indicates a need to investigate information sources. The aims of this study were to analyse consumer-focused introduction to solids resources and explore mothers’ awareness and use of Australian Infant Feeding Guidelines (AIFG) with the aim of developing some future recommendations for resource development and dissemination. Resources were identified from government, non-government and other providers, and content analysis was applied using the validated Suitability Assessment of Material score sheet to identify weaknesses and readability level was calculated. An online survey using a semiquantitative questionnaire was distributed via Facebook to explore mothers’ feeding experiences and use of resources in 2015. Twenty-five resources were identified and government resources were more likely to be scored superior in format and content. The content of all resources supported the 2013 AIFG but the majority had readability levels higher than 6th reading grade. Cultural appropriateness category mean score (61%) across all three groups. Survey results from 93 women found only 29% of mothers had heard of the AIFG and they confirmed their major source of helpful information was Internet (55%) and friends (45%). Mothers identified that they would prefer to receive information via health professionals (36%), the web (29%) and pamphlets (15%). Dietitians have a future role in resource development to ensure suitable readability and cultural relevance. Dietitians need to develop skills in using the web and social networks to disseminate key health messages relating to the introduction of solids.